2018
DOI: 10.12911/22998993/89651
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Photocatalytic Decomposition of Bisphenol A on Modified Photocatalysts

Abstract: This paper presents the evaluation of the photocatalytic kinetics of bisphenol A decomposition in the presence of commercial titanium(IV) oxide and modified photocatalysts (composites). The following modification methods were used: mechanical mixing, calcination and impregnation. The decomposition process was carried out with the addition of photocatalysts and activated carbon at doses of 100 mg/dm 3 and 25 mg/dm 3 , respectively. The photocatalytic process was performed in a reactor from the Heraeus Company (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…On the other hand, holes will oxidize the hydroxyl to produce a radical with more energy large, such as hydroxyl radicals. These hydroxyl radicals will break down contaminants organic into harmless green compounds that are environmentally friendly (Zawadzki et al, 2018). This statement is in accordance with a research review by Ong Comparison of degradation values at optimum conditions using a UV lamp and without a UV lamp at different pH (pH 6-8) can be seen in Figure 4 and 5.…”
Section: Effect Of Ultraviolet Irradiation In Degradation Of Heavy Me...supporting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, holes will oxidize the hydroxyl to produce a radical with more energy large, such as hydroxyl radicals. These hydroxyl radicals will break down contaminants organic into harmless green compounds that are environmentally friendly (Zawadzki et al, 2018). This statement is in accordance with a research review by Ong Comparison of degradation values at optimum conditions using a UV lamp and without a UV lamp at different pH (pH 6-8) can be seen in Figure 4 and 5.…”
Section: Effect Of Ultraviolet Irradiation In Degradation Of Heavy Me...supporting
confidence: 88%
“…Heavy metals Cu, Fe, and Pb reported the highest degradation percentages after 60 minutes under optimal conditions using ultraviolet radiation. The primary chemical characteristic of the photocatalytic process is the generation of hydroxyl radicals, which act as oxidizers for organic contaminants (Zawadzki et al, 2018). Previous study by Prasetyaningrum et al (2020) has shown that the use of UV irradiation treatment can significantly boost the reduction of heavy metal pollutants, such as copper (Cu), ion electroplating wastewater by around fifty percent.…”
Section: Effect Of Ultraviolet Irradiation In Degradation Of Heavy Me...mentioning
confidence: 99%
“…Photocatalysis with the combination of the ZnO photocatalyst and synthetic zeolite adsorbent is more effective and the result of pollutant degradation is maximized. The common chemical feature in the photocatalytic process is the hydroxyl radicals formation as an oxidizer of organic pollutants (Zawadzki et al, 2018). The photodegradation method is cheaper and easy to apply (Agustina et al, 2020).…”
Section: The Degradation Results With a Uv-vis Spectrophotometermentioning
confidence: 99%
“…Satisfactory fitting (60-80%) was obtained only for the H 2 O 2 process, as a result of the very low RhB degradation effectiveness (under 1%). A phenomenon characteristic of advanced oxidation processes is the occurrence of (typically) two time intervals for the conducted oxidation reactions [38]. Other authors [39,40] observed a similar phenomenon as well, resulting most likely from the indirect reactions of oxidizing components with the pollutant degradation products.…”
Section: Kinetics Studiesmentioning
confidence: 79%